Assessment Of Key Markets For Institutional Investors In Ukraine In The Context Of War - Volodymyr Vazhynskyi; Микола Погорецький; Toporetska, Zoriana (Izdevniecība “Baltija Publishing”, 2023)
The article is devoted to the assessment of key markets for institutional investors in Ukraine in the context of Russia's full-scale invasion. The purpose of this study is to assess the institutional investor market in Ukraine during the war. To achieve this goal, it is necessary to solve the following tasks: to study the legal status of an institutional investor in Ukraine and its types, to assess changes in the institutional investor market after the start of a full-scale invasion, to identify key risks that exist in the market now, and to provide proposals on the need to improve state regulation of the institutional investor market to protect citizen investors in times of war. The methodological basis of the study was formed by general scientific methods of cognition: the dialectical method of cognition of the phenomena of the surrounding reality and the comparative legal method for establishing the legal status of an institutional investor, methods of logic (analysis, synthesis, induction, deduction, analogy), economic analysis, absolute and comparative advantages and statistical methods for analysing the market of institutional investors and making proposals, mathematical methods for calculating the volume of the market of institutional investors. In accordance with the systemic and structural approach, the institutional investor market was assessed by each of the structural elements of this market. The authors propose to consider an institutional investor as a financial intermediary that attracts and accumulates funds of individual investors (consumers of financial services) and carries out investment activities in the interests of individual investors aimed at financing socially and economically important sectors of the economy for the state and society. The authors pay special attention to the concept of responsible business conduct, pointing out that today, socially responsible business conduct is extremely important for the activities of an institutional investor, which includes "responsible attraction (accumulation) of funds" and "responsible spending (investment) of investors' funds". The study found that the main markets for institutional investors in Ukraine – banking, insurance and private pensions – showed stability and a slight increase in key indicators, which is very positive for Ukraine today. However, in the long term, there are a number of risks that should be taken into account by the government when formulating the state policy on the activities of institutional investors in these markets to protect the interests of citizen investors. The article provides suggestions on the main areas of improvement of the legislation on the activities of institutional investors to minimise the risks of citizen investors.
Keywords: investment activity; institutional investor; sk assessment; banks; government regulation; non-state pension funds